Landscape element assessment of Melaka historic waterfront through the review on the impression of place - Hussain, Mohd Amirul (2016)
Malaysia has lots of historic waterfront from Peninsular Malaysia until Sabah and Sarawak. Unfortunately, these historic waterfronts are less attention from Malaysians as a favorite destination for vacation. This problem caused by weaknesses of landscape element provided along the waterfront that cannot create the impression of places. According to the problem, this research aim is to concentrate on reviewing the ability of landscape element at Melaka historic waterfront to enhance the impression of places. Thus, it will accentuate our local tourism sector at the historic waterfront area. The qualitative method was used to fulfill the research objectives and also to gain the data collection. The Melaka historic waterfront was selected as a study location to evaluate the impression of its place. The finding of the research proposed a landscape element framework for the Melaka historic waterfront that portrays a vibrant design concept of landscape element that can enhance the impression of place. Furthermore, this landscape element framework can be used as a reference to urban planner, landscape architecture, architecture, local authority and related field in planning a vigorous historic waterfront at Malaysia. It will enhance the local tourism activities and economic sector.